Increased extreme precipitation in Chinese deserts from 1960 to 2018 - Guoshuai Li; Hong Yang; Ying Zhang; Chunlin Huang; Xiaoduo Pan; Mingguo Ma; Minhong Song; Q H Zhao (PANGAEA, 2019)
Extreme precipitation over drylands, especially deserts, has been often observed. The precipitation changes in Chinese deserts have been rarely studied. Here, we use a daily grid precipitation dataset generated via weather station data (0.25° horizontal grid spacing) to investigate the spatial and temporal changes in extreme precipitation in Chinese deserts. The extreme precipitation based on the changes in the total precipitation (PRCPTOT) and the annual-maximum daily precipitation (Rx1day) in the Chinese desert exhibits markedly increasing trends and presents a spatial distribution of wetting in the western deserts and drying in the eastern deserts. The increase in extreme precipitation could minimize wind erosion and intensify dune stabilization in the western Chinese deserts.
Supplement to: Li, G et al. (2019): More Extreme Precipitation in Chinese Deserts From 1960 to 2018. Earth and Space Science (ESS), 6(7), 1196-1204, https://doi.org/10.1029/2018EA000538